オホーツク海のメタンハイドレートとプルーム - 庄子, 仁; JIN, Young K; OBZHIROV, Anatoly; SALOMATIN, Alexander; BARANOV, Boris; GLADYSH, Vyacheslav; 八久保, 晶弘; 南, 尚嗣; 山下, 聡; 高橋, 信夫 (Chigaku Zasshi (Jounal of Geography), 2009)
Methane hydrates exist beneath the sea bottom near cold seeps NE off the Sakhalin in the Sea of Okhotsk. Multidisciplinary field operations were performed at a study area （approximately 16 × 20 km2）to investigate seepage characteristics and understand gas hydrate formation mechanisms. A continuous profiling survey was conducted to obtain a distribution map of seepage structures on the floor by using a deep-tow, side-scan-sonar equipment. The distribution map reveals that the dense area of seepage structures coincides with a sea-floor area of deformed sediments caused possibly by repeated sediment slumping and debris flows in the past. We speculate that this deformation may have created shallow faults that are suitable to conduits for the migration and discharge of gas and fluid. Three seepage structures were selected to study about their fluid-seep conditions around the sea floor level. Hieroglyph seepage structure is located at the northern end of the dense area of the structures. Kitami and Chaos structures are located about 2 and 7 km respectively apart from the Hieroglyph structure within the dense area. Large plumes on echograms and higher methane contents in the water column confirm gas seepage activities at the three structures. There observed at least two and four plumes at the Hieroglyph and Chaos structures, respectively. Each gas chimney image in seismic reflection profiles was traced to connect each BSR and seepage structure. Both pull-up and disturbed structures of BSR around the gas chimney images were interpreted as to be indications of significant heat flows caused by ascending fluid at both Kitami and Chaos structures. On the other hand, almost no pull-up/disturbance of BSR was observed at the Hieroglyph structure, suggesting little water seepage. The seep activity may vary with time off the Sakhalin. The Hieroglyph structure is located at the edge of a dense area of the seepage structures. It might serve as an indicator for the longterm activity of the fluid seepage system off the Sakhalin. ...